Antistreptokinase antibodies: implications for thrombolysis in a region with endemic streptococcal infection. Issue 9 (26th August 2005) - Blackwell, N; Hollins, A; Gilmore, G; Norton, R
Abstract : Aims: To determine antistreptokinase antibody (anti-SK) titres in patients with the acute coronary syndrome from communities with endemic group A streptococcal infection because of the implications for streptokinase (SK) thrombolysis. Methods: Anti-SK titres were determined using a standard method in 47 consecutive SK naive patients, presenting to the Mt Isa Hospital emergency department, Australia, with an acute coronary syndrome. Both indigenous and non-indigenous subjects were enrolled. Antistreptolysin O (ASOT) and anti-DNAse B (ADB) titres were also determined. Results: Indigenous patients were more likely to have anti-SK antibodies (p < 0.001) than the non-indigenous cohort. Anti-SK antibody titres also correlated well with ASOT/ADB titres. Conclusions: Anti-SK antibodies are highly prevalent in SK naive indigenous patients presenting with the acute coronary syndrome. Streptokinase should not be used for thrombolysis in populations with endemic group A streptococcal infection.